Zoonotic Infections in Communities of the James Bay Cree Territory: An Overview of Seroprevalence. Issue 2 (2013) - Sampasa-Kanyinga, Hugues; Lévesque, Benoit; Anassour-Laouan-Sidi, Elhadji; Côté, Suzanne; Serhir, Bouchra; Ward, Brian J; Libman, Michael D; Drebot, Michael A; Makowski, Kai; Dimitrova, Kristina; Ndao, Momar; Dewailly, Éric
Abstract : The Cree communities of James Bay are at risk for contracting infectious diseases transmitted by wildlife. Data from serological testing for a range of zoonotic infections performed in the general population (six communities), or trappers and their spouses (one community), were abstracted from four population-based studies conducted in Cree territory (Quebec) between 2005 and 2009. Evidence of exposure to Trichinella species, Toxoplasma gondii, Toxocara canis, Echinococcus granulosus, Leptospira species, Coxiella burnetii and Francisella tularensis was verified in all communities, whereas antibodies against Sin Nombre virus and California serogroup viruses (Jamestown Canyon and snowshoe hare viruses) were evaluated in three and six communities, respectively. Seroprevalence varied widely among communities: snowshoe hare virus (1% to 42%), F tularensis (14% to 37%), Leptospira species (10% to 27%), Jamestown Canyon virus (9% to 24%), C burnetii (0% to 18%), T gondii (4% to 12%), T canis (0% to 10%), E granulosus (0% to 4%) and Trichinella species (0% to 1%). No subject had serological evidence of Sin Nombre virus exposure. These data suggest that large proportions of the Cree population have been exposed to at least one of the targeted zoonotic agents. The Cree population, particularly those most heavily exposed to fauna, as well as the medical staff living in these regions, should be aware of these diseases. Greater awareness would not only help to decrease exposures but would also increase the chance of appropriate diagnostic testing.